2022
DOI: 10.1186/s12891-021-04981-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of health-related quality of life changes (EQ-5D and EQ VAS) after total hip and knee replacement: a systematic review

Abstract: Background Patient-reported outcomes are of ever-increasing importance in medical decision-making. The EQ-5D is one of the generic instruments measuring health-related quality of life (HRQoL) in arthroplasty. This review aimed to identify possible predictors of HRQoL changes for patients undergoing total knee replacements (TKR) or total hip replacements (THR). Methods A systematic literature review according to the PRISMA guidelines was conducted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Recent studies confirmed this high responsiveness of the EQ-5D in knee arthroplasty ( 41 ). It is still unclear whether patient characteristics have an influence on changes in the EQ-5D Index after arthroplasty, a clear effect has so far only been shown for body mass index ( 42 ). The negative effect size shown in our study for femur fracture confirms other meta-analytic findings that older patients with hip fracture in particular do not experience a full recovery of their HRQoL to baseline values ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed this high responsiveness of the EQ-5D in knee arthroplasty ( 41 ). It is still unclear whether patient characteristics have an influence on changes in the EQ-5D Index after arthroplasty, a clear effect has so far only been shown for body mass index ( 42 ). The negative effect size shown in our study for femur fracture confirms other meta-analytic findings that older patients with hip fracture in particular do not experience a full recovery of their HRQoL to baseline values ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as with functional knee outcome, the follow-up questionnaire being at one year may have meant any effect on HRQoL attributable to post-operative pain-management technique may be masked by other factors. Post-operative EQ-5D has been shown to be predicted by age, sex, education, obesity, socioeconomic status, anxiety and depression [ 22 ]. A regression analysis was completed including available confounding factors in our study (sex, socioeconomic group, ASA grade, pre-operative functional scores), and there remained no significant difference in EQ-5D change between groups.…”
Section: Discussionmentioning
confidence: 99%
“… 29 The EQ-VAS is a scale on which a patient rates their current health ‘today’ from 0 (the worst imaginable health) to 100 (the best imaginable health), with an estimated MCID between 6.4 and 15 points. 30 , 31 …”
Section: Methodsmentioning
confidence: 99%